(untitled) (Papeles, 2024)
The development of new forms of work based on technology makes it necessary to acknowledge digital clues of employment. In this essay, a return to the Marxian theory of alienated labor is proposed as the beginning of this development, applying the same concepts that Marx used for commodities to the treatment of data.